Avaliação de métodos de lise celular de sporobolomyces ruberrimus - Pennacchi, Mariana Gomes Clemente (2014)
Carotenoids are important biomolecules of economic interest due to biological properties that show. They can be synthesized by plants and microorganisms, among which stand out the red yeast. The recovery process of these intracellular pigments involves a crucial stage of cell lysis. Thus, the present study aimed to evaluate different methods of yeast cell lysis (Sporobolomyces ruberrimus) in order to optimize the recovery of intracellular pigments. The first stage of the research, conducted through a 23 factorial design with central point sought to evaluate which of the parameters investigated (cell concentration, gradient of lysing agent and stirring speed) affect, more significantly, the amount of total carotenoids recovered. The initial study indicated that the research should be performed with a fixed cell concentration. So, from these results, it was defined cell concentration of 500 mg / L and the new 22 factorial design with central point was set. The independent variables applying vortex + lysing agents were optimized for the conditions studied in 135 mg of glass beads and 1230 rpm stirring speed to vortex + glass beads method. Already the chemical method 'classic' (dimethylsulfoxide) considered by the literature presented as significant independent variable only the concentration of lysing agent whose optimum value found was 2,7 mL DMSO. The same planning and conditions were applied on the use of planetary mill, where the efficiency of the process is independent of any of the parameters evaluated, enabling the use of milder processing conditions (135 mg extracting agent and 200 rpm of stirring speed). As for the cell lysis, direct microscopic analysis indicated that mechanical methods for cell lysis studied were more efficient in the laceration of the cells and that the extraction of intracellular carotenoids employing the chemical method with DMSO possibly occurs just by cell permeabilization.